Study of the Peptizability of Boehmite and Its Application for the Formation of γ-Al2O3 in Spherical Shape - Tran Dai Lam; Pham Thanh Huyen; Nguyen Han Long (ASEAN Journal of Chemical Engineering, 2007)
This paper shows the results of the peptizability of boehmite and its application for the formation of γ-Al2O3 in spherical shape. The obtained γ-Al2O3 in spherical shape have high mechanical strength and high surface area. The water vapor adsorption ability of sphere of γ-Al2O3 has also been determined. The γ-Al2O3 in spherical shape can adsorb moisture up to 65% of their weight.